Sustainable Development and the Transformation of Female Rural Labor:: the Case of Women Cattle Ranchers in Uruguay (Sustainability in Debate, 2014)
Although rural woman are usually considered key to sustainable development at the internationallevel, their work in cattle-raising continues to be under-recognized by most policymakers fromUruguay. This fact has forced many young women to migrate towards urban areas, leading tothe “masculinization” of Uruguayan cattle-raising. National statistics tend to ignore unpaidactivities performed by rural women ”“ which they consider as “non-productive”-, as well aswomen’s evolving role in cattle-raising. By using semi-structured interviews and participantobservation, this work analyzed: i) the organization of work of women in family farms devoted tobeef and milk production Uruguay, including the role of chiefs, co-chiefs and passive observers,ii) their decision-making processes, and iii) their personal insights about cattle-raising. Five factorswere identified as key to their work profiles: family relations, socio-economic status, size of theproductive unit, presence of permanent employees, and formal land and/or cattle tenure.